Assessment of Solar Energy Resource for PV Plant Development Using a Low-cost PV Monitoring System - Alfeus Sunarso; Devi Andriani; Dovian Iswanda; Nurhaidah Nurhaidah; Tri Pratomo; Halasan Sihombing; Yunita Yunita; Wendhi Yuniarto; Rusman Rusman (Faculty of Engineering, Universitas Tanjungpura, 2023)
In this work, we propose the use of a low-cost PV monitoring system for providing accurate and comprehensive data required in the development of efficient and reliable solar PV plants. The system is developed based on an open-source Arduino platform with the capability to monitor solar irradiance, and electric outputs and temperature of multiple solar panels, which should enable the accurate assessment of solar energy resource, as well as electrical energy produced by PV plant under real operating conditions. To demonstrate its applicability, the system has been installed at the campus of Politeknik Negeri Pontianak in Pontianak City, and the data collected by the system is used to assess solar energy resource at the location. Data collected by the system from August 2020 to September 2021 shows that the values of solar irradiation are in the range of 2.9–4.1 kWh/m2 per day, and electric energy produced by commercial solar panels are in the range of 0.30–0.46 kWh/m2 per day, correspond to the monthly averaged efficiencies of 8–13%. The values of solar irradiation are 15–40 % lower than those obtained from the space-averaged satellite data which are in the range of 4.1–5.8 kWh/m2 per day. This shows the significant effects of local conditions, and confirms the advantage of assessment using the low-cost monitoring system that directly accounts for the effects of local conditions without the need of simulation using complex model and sophisticated software that required in the assessment using satellite-derived data.